2022
DOI: 10.1029/2022ja030661
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Long‐Duration High 2‐MeV Electron Flux Periods in the Outer Radiation Belt

Abstract: Since the advent of the Space Age, the importance of understanding and forecasting relativistic electron fluxes in the Earth’s radiation belts has been steadily growing due to the threat that such particles pose to satellite electronics. Here, we provide a model of long‐duration periods of high time‐integrated 2‐MeV electron flux deep inside the outer radiation belt, based on the significant correlation obtained in 2001–2017 between time‐integrated electron flux measured by satellites and a measure of the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 122 publications
1
16
0
Order By: Relevance
“…Since the relativistic electron fluxes are the cumulative result of acceleration processes that take hours to days, statistical studies by Mourenas et al. (2019, 2022) demonstrated that time‐integrated geomagnetic indices were more informative in predicting outer belt electron dynamics than instantaneous values. Specifically, Mourenas et al.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the relativistic electron fluxes are the cumulative result of acceleration processes that take hours to days, statistical studies by Mourenas et al. (2019, 2022) demonstrated that time‐integrated geomagnetic indices were more informative in predicting outer belt electron dynamics than instantaneous values. Specifically, Mourenas et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Mourenas et al. (2022) constructed a predictive model of high time‐integrated 2‐MeV electron fluxes using a time‐integrated aa H index. Nevertheless, the studies of Mourenas et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations